Linguistic Features in E-commerce Slogans - Luluk Iswati; Pratomo Widodo (Indonesian Journal of EFL and Linguistics, 2020)
Slogan is one of the powerful tools to advertise e-commerce products and services. The power of slogan to promote commodities lies primarily on the language style that it employs. This study is aimed at analyzing the linguistic feautures in 38 e-commerce slogans that are popular in Indonesia. The data were analyzed quantitatively and qualitatively. Quantitatively, the data were calculated regarding the frequency of each identified linguistic features: semantic devices, syntactic devices, phonetic devices, orthographic devices, syntactic errors, code-mixing, and moods. Qualitatively, the data were verbally analyzed, described, and discussed. The findings show that regarding linguistic devices, the most prevalent case is semantic device (self-reference). Concerning syntactic errors, the most apparent errors relate to word order typology and ommission of articles & prepositions. Speaking of code-mixing, the most frequently used term is the word ‘online’. In relation to moods, the most dominant mood is declarative. This study suggests further study with a wider context of data